A review on ultimate strength of aluminium structural elements and systems for marine applications - Hosseinabadi, Omid Ferdowsi; Khedmati, Mohammad Reza (Ocean engineering, 2021)
Nowadays, aluminium alloys are very popular for use in the marine industry. One of the most important applications of aluminium in the marine industry is the construction of high-speed vessels. With the expansion of the role of high-speed vessels, applying ultimate strength based design methods for structural design and optimization of aluminium vessels' is getting more attention. Formulations developed for steel structures' ultimate strength prediction cannot be used directly for aluminium alloys' structures. This is mainly due to the different nature of various aluminium alloys' material behaviour in terms of stress-strain relationship compared to steel. Besides, initial imperfections generated during fabrication, including initial deflections, residual stresses, and softening of material in the heat-affected zone, make a significant difference between aluminium alloys and steel structures. Many research studies employed various methods for the investigation of aluminium structures’ ultimate strength. These studies mainly focused on understanding the effects of different parameters. This paper reviews parameters such as stress-strain relationship, initial imperfections, boundary conditions, and extent of analysis which affects the ultimate strength of aluminium ship hull girder elements. The concluding remarks of this paper are reviewed in a comparative manner such that it can be used as a reference for future studies. •Ultimate strength behaviour of aluminium ship structural elements is reviewed.•Methods and parameters involved in ultimate strength of aluminium ship structural elements are tabulated.•Summary tables provide convenient means to assess the effects of different methods and parameters.